Protocol for an open label: phase I trial within a cohort of foetal cell transplants in people with Huntington's disease. Issue 1 (19th January 2021) - Drew, Cheney J G; Sharouf, Feras; Randell, Elizabeth; Brookes-Howell, Lucy; Smallman, Kim; Sewell, Bernadette; Burrell, Astrid; Kirby, Nigel; Mills, Laura; Precious, Sophie; Pallmann, Philip; Gillespie, David; et al.
Abstract: Huntington's disease is a progressive neurodegenerative disorder characterized by motor, cognitive and psychiatric symptoms. Currently, no disease-modifying therapies are available to slow or halt disease progression. Huntington's disease is characterized by relatively focal and specific loss of striatal medium spiny neurons, which makes it suitable for cell-replacement therapy, a process involving the transplantation of donor cells to replace those lost due to disease. TRIal DEsigns for delivery of Novel Therapies in neurodegeneration is a phase I Trial Within a Cohort designed to assess safety and feasibility of transplanting human foetal striatal cells into the striatum of people with Huntington's disease. A minimum of 18 participants will be enrolled in the study cohort, and up to five eligible participants will be randomly selected to undergo transplantation of 12–22 million foetal cells in a dose escalation paradigm. Independent reviewers will assess safety outcomes (lack of significant infection, bleeding or new neurological deficit) 4 weeks after surgery, and ongoing safety will be established before conducting each subsequent surgery. All participants will undergo detailed clinical and functional assessment at baseline (6 and 12 months). Surgery will be performed 1 month after baseline, and transplant participants will undergo regular clinical follow-up for at least 12 months. Evaluation of trial processes will also be undertaken. Transplant participants and their carers will be interviewed ∼1 month before and after surgery. Interviews will also be conducted with non-transplanted participants and healthcare staff delivering the intervention and involved in the clinical care of participants. Evaluation of clinical and functional efficacy outcomes and intervention costs will be carried out to explore plausible trial designs for subsequent randomized controlled trials aimed at evaluating efficacy and cost-effectiveness of cell-replacement therapy. TRIal DEsigns for delivery of Novel Therapies in neurodegeneration will enable the assessment of the safety, feasibility, acceptability and cost of foetal cell transplants in people with Huntington's disease. The data collected will inform trial designs for complex intra-cranial interventions in a range of neurodegenerative conditions and facilitate the development of stable surgical pipelines for delivery of future stem cell trials. Trial Registration: ISRCTN52651778 Abstract : The TRIDENT trial uses a 'Trial Within a Cohort' design to assess the safety and feasibility of escalating doses of foetal cells in participants with Huntington's disease. This study focuses on addressing the many of constraints facing evaluation of advanced, non-pharmacological therapies in this and other neurodegenerative diseases. Graphical Abstract: